Evidence for a role of protein kinase C zeta subspecies in maturation of Xenopus laevis oocytes. - Dominguez, I (1992)
A number of studies have demonstrated the activation of phospholipase C-mediated hydrolysis of phosphatidylcholine (PC-PLC) both by growth factors and by the product of the ras oncogene, p21ras. Evidence has been presented indicating that the stimulation of this phospholipid degradative pathway is sufficient to activate mitogenesis in fibroblasts as well as that it is sufficient and necessary for induction of maturation in Xenopus laevis oocytes. However, the mechanism whereby PC-PLC transduces mitogenic signals triggered by growth factors or oncogenes remains to be elucidated. In this study, data are presented that show the involvement of protein kinase C zeta subspecies in the channelling of the mitogenic signal activated by insulin-p21ras-PC-PLC in Xenopus oocytes as well as the lack of a critical role of protein kinase C isotypes alpha, beta, gamma, delta, and epsilon in these pathways.